Typification and novelties in Rubiaceae for the flora of Vietnam - Hong Quang, Bui; Duc Binh, Tran; Ngoc Diep, Tran Thi; Thuy Duong, Tran Thi; Tuan Anh, Le (Academia Journal of Biology, 2023)
Four Rubiaceous species viz. Hedyotis diversifolia, Involucrella lithophila, Mouretia larsenii, Ophiorrhiza cana are newly recorded for the flora of Vietnam. Morphology based identification key, taxonomic notes, and photo-plates of the newly reported species are provided. Moreover, the second-step lectotype has been designated for the name Involucrella chereevensis. These findings provide some new basic data essential for biodiversity research in Vietnam. key, taxonomic notes, illustration provided.